Ceux qui sauront : le déclinisme uchronique de Pierre Bordage - Ainseba, Tayeb (2018)
“What if the French Revolution had never happened? What if what seems to be France's greatest pride was simply erased from history books? These are the questions that haunt Pierre Bordage's alternate history fiction Ceux qui sauront (Those who know) which was published in 2008 and is the first volume of a trilogy (Ceux qui rêvent (Those who dream), 2010; Ceux qui osent (Those who dare), 2012). Bordage does not outline all the political ramifications of this null and void revolution but his narrative is centred on the prohibition of teaching for the enduring Third Estate. Even though it has been labelled children's literature, this work of alternate history is full of violent declinism: it tackles both the State's misology and the way scholars are disdained within a mercantile order, it denounces the way politics have abandoned the social and the way school has been forced to secrecy. Given these declinist characteristics, might we not classify this alternate history as a distopia? What are the whys and the wherefores of this all-French anti-humanism? What does this work reveal as regards contemporary, end of twentieth, beginning of twenty-first century France?